Antecedents and Consequences of Public Procurement Non-compliance Behavior - Tukamuhabwa, Benjamin R. (Journal of Economics and Behavioral studies, 2012)
This paper proposes a conceptualization of the antecedents and consequences of compliance/ non-compliance behaviour in public procurement. It was motivated by the paucity of studies on public procurement compliance in Uganda, despite the evidently rampant non-complaint behaviour exhibited and a realization by recent researchers that less research has been conducted on organizational misbehaviors and non-compliance in purchasing and supply management. There are also scanty (if any) studies that have incorporated antecedents and consequences of public procurement compliance in a comprehensive single framework such as proposed in this study. Through a review of existing scholarly works, documents, records and reports, a conceptual frame work was developed in which media publicity, enforcement, records management, organizational culture, political interference, professionalism, organizational incentives, perceived rule legitimacy, moral obligation, social influence, familiarity with rules and top management support were identified as antecedents while cognitive dissonance, low employee motivation, low corruption, better corporate governance and low service delivery were established as consequences. It is hoped that future researchers will utilize the current proposed conceptual model to conduct empirical studies on public procurement compliance in Uganda and other geographical contexts. This will provide practical implications that will assist to avert the unbridled squander of colossal amount of money through flouting public procurement procedures.
Keywords: Conceptual framework; Public procurement; Rules; Compliance